An experimental design and implementation protocol for testing a dashboard for improving sustainable healthy food choice - Mariana Moncada de la Fuente; Ebenezer M. Kwofie; Prince Agyemang; Marie-Anne Dessureault; Ghina El Haffar; Laurette Dube; Stan Kubow; Valerie Orsat (MethodsX)
Within the last decade, one of the crucial efforts to reduce environmental impact and improve consumers' health has focused on shifting food choices. In our previous study, the authors developed a customizable and adaptable Dashboard for Improving Sustainable Healthy (DISH) food choices. DISH leverages nudge and traffic-light labels to enable consumers to compare and envision the potential environmental, nutritional, and health impacts of their food choices before purchasing. An initial test among 112 individuals through an online survey revealed the potential of the tool to shift purchase intentions among consumers on a university campus. As part of a second phase in a series of consumer evaluations, we provide a step-by-step protocol followed to investigate the effectiveness of a version of DISH (McGill DISH) in stimulating subtle dietary changes on another university campus. • Environmental nutrition information on DISH was communicated in simple but intuitive ways through multiple technological media (self-service kiosks and mobile applications) to stimulate dietary change. • The study participants were randomly separated into treatment and control groups. • We hypothesize that the participants in the treatment group are more likely to engage with food products that are more sustainable and healthier on the DISH application compared to the control group.